Elusive Phenomena, Unwieldy Things Historical Perspectives on Experimental Control - Schickore, Jutta; Newman, William R. (Archimedes, New Studies in the History and Philosophy of Science and Technology,, 2024)
This open access book provides a historical treatment of scientific control in experimentation in the longue durée. The introduction distinguishes four related strands in the history of experimental control: the development of practices to stabilize experimental conditions; the career of the comparative design; the unfolding of methodological discussions about control practices and designs; and the history of the term "control". Each chapter brings these distinctions to bear on specific historical episodes. The focus is on experiments with complex, elusive phenomena such as perception and learning, irregular movements, and unobservable elements. Such experiments bring control issues to the fore because they are difficult to design and stabilize and often controversial. Together, the chapters show that the local context shapes what exactly is controlled, how control can be accomplished, and how controls are justified. They also show that control strategies and methodological ideas often remain stable for a long time and change only gradually. This book, as well as the volume on analysis and synthesis in experimentation by the same editors, contains contributions by an array of experts from multiple disciplines, making it suitable for historians and philosophers of science and students alike.